Significance of whole genome sequencing for surveillance, source attribution and microbial risk assessment of foodborne pathogens. (April 2016) - Franz, Eelco; Gras, Lapo Mughini; Dallman, Tim
Highlights: WGS is mainly being applied for surveillance and outbreak investigation purposes. There is a strong need for harmonization of typing methods and nomenclature. WGS is poorly exploited in source attribution and microbial risk assessment. New modelling approaches able to handle the high resolution of WGS data are needed. Defining research questions beforehand is crucial for proper WGS data analysis. Abstract : As the whole genome sequencing (WGS) revolution is rapidly gaining momentum, it is essential to understand the significance of this technology and its future applications in food safety. This review discusses the recent advances concerning the use of WGS for outbreak detection and surveillance, microbial source attribution and microbial risk assessment. Although the WGS is mainly being applied for surveillance and outbreak investigation purposes, there is still, a strong need for harmonization of methods (sample preparation, sequence quality and case-definition, analysis) and consensus on suitable nomenclature (SNP versus allele level)and case definition. The application of WGS in source attribution and microbial risk assessment is largely unexplored. The use of WGS in source attribution requires the development of new modelling approaches that can handle the large amount of data and the high discriminatory power associated with WGS. For microbial risk assessment, the link with phenotypic features is crucial, but the short-comings regarding the reproducibility of genome-wide-association studies and the link to epidemiology need innovative statistical approaches. Overall, WGS data alone are of limited use without a sound public health or biological context. Defining hypotheses and research questions beforehand are crucial for the correct analysis and interpretation of WGS data.